Emotion and Cognition Risk and Reward of Digital Scrolling among Emerging Adult - Meilani Sandjaja; Cicilia Larasati Rembulan (Utan Kayu Publishing, 2026)
Previous studies have largely examined the positive and negative impacts of social media use. This research broadens the scope to a wider behavioral pattern, namely digital scrolling behavior. Unlike earlier studies that employed the instant gratification theoretical framework, this study applies the instant gratification theory to identify the triggering situations that drive young adults to engage in digital scrolling behavior and to explore the dynamics that occur once they have obtained instant gratification. Adopting a qualitative approach, this study offers novelty compared to prior research that predominantly relied on quantitative methods. Data were collected from 309 personal diaries completed over one month by 65 young adults and analyzed thematically. The findings reveal situational factors triggering digital scrolling behavior, including activity-related, emotion- related, and external-related situations. Instant gratifications obtained include entertainment, product discovery, inspiration, escape from problems, and access to information. Participants reported both positive and negative emotional outcomes. Typically, digital scrolling was triggered by specific situations, leading to instant gratification and positive emotions. However, when digital scrolling behavior is unregulated, these positive emotions shift into negative ones. This study contributes novelty by providing deeper insights into scrolling behavior through the lens of instant gratification theory, highlighting the triggering situations, and the dynamic of its dual emotional consequences.